Catholic social teaching, sustainable development and social solidarism in the context of social security - Stanisław Adamiak; Damian Walczak (Copernican Journal of Finance & Accounting, 2014)
Nowadays, opposite to what could be observed at the end of the nineteenth century, people are more focused on creating larger societies rather than sets of alienated individuals. Certainly, there are many factors that cause this kind of trend. The factors may include social determinants known as Catholic social teaching, social solidarism and sustainable growth. Each of the above factors refers to the three methods of social security, whose aim is to protect citizens against the threat of unsatisfied basic needs, socially recognized as valid. Catholic social teaching, social solidarism and sustainable growth refer both to obliging the state to help people who are facing a situation of unsatisfied basic needs (do not allow the possibility of leaving the individual alone – the procurement method) and to indicating everyone the necessity of self-protection that reaches above the minimum guaranteed by the state (the insurance method). Also, they indicate the possibility (necessity) of functioning in society a kind of support provided to persons in need from voluntary payments (institutions or individuals – the philanthropic method).